Comparison of behaviors regarding live poultry exposure among rural residents in Vietnam and Thailand - Liao, Qiuyan; Lam, Wendy Wing Tak; Bich, Tran Huu; Dang, Vu Trung; Fielding, Richard (The Journal of Infection in Developing Countries, 2014)
Introduction: Live poultry exposure and risk behaviors are more prevalent in rural communities, increasing the risk of influenza A/H5N1 infection. We examined the economic and socio-cultural influences on poultry-related practices by comparing the poultry-related practices among Vietnamese and Thai rural residents by family income and consumption preference. Methods: Stratified cluster sampling was performed to select households. Within each household, one adult was randomly selected for a face-to-face interview in five Vietnamese and five Thai rural districts. Using a standardized questionnaire to assess domestic poultry husbandry, live poultry purchase, and demographics, logistic regression enabled comparisons of behaviors related to live poultry exposure and examination of associated factors. Results: Among 994 Vietnamese and 907 Thai rural residents, live poultry exposure (prevalence of raising poultry, improper handling of sick or dead poultry, touching live poultry before buying, and slaughtering poultry at home) was more prevalent among Vietnamese than Thai respondents. After adjusting for other demographics, respondents with higher family incomes were less likely to rear backyard poultry in both Vietnam and Thailand, and with more likely to buy live poultry in Vietnam, but not in Thailand. Consumption preference for live poultry was associated with being more likely to rear backyard poultry in Vietnam and Thailand, and with being more likely to buy live poultry in Thailand, but not in Vietnam. Conclusion: The findings suggest important roles of economic imperatives and cultural preference for live poultry for consumption in supporting poultry rearing and live poultry purchase among rural residents.